Psychological treatments in schizophrenia: II. Meta-analyses of randomized controlled trials of social skills training and cognitive remediation. - Pilling, S; Bebbington, P; Kuipers, E; Garety, P; Geddes, J; Martindale, B; Orbach, G; Morgan, C (2002)
BACKGROUND: Social skills training and cognitive remediation are psychological techniques with considerable face validity for the treatment of negative symptoms of schizophrenia and their consequences. This paper provides a meta-analytical review of these treatments. It includes an appreciable number of randomized controlled trials, using comparisons against both standard care and other active interventions. However, the assessment of particular outcomes sometimes had to be based on single studies. METHOD: A detailed search strategy was used to identify randomized controlled trials of social skills training and cognitive remediation, primarily employing electronic databases. Randomized controlled trials (RCTs) that met predefined criteria were then subjected to meta-analysis on a variety of outcome measures. RESULTS: There was no clear evidence for any benefits of social skills training on relapse rate, global adjustment, social functioning, quality of life or treatment compliance. Cognitive remediation had no benefit on attention, verbal memory, visual memory, planning, cognitive flexibility or mental state. CONCLUSIONS: Social skills training and cognitive remediation do not appear to confer reliable benefits for patients with schizophrenia and cannot be recommended for clinical practice.